The Development Of Mctim (Multicultural Textile Interactive Module) Using Delphi Technique - Ahamed Kamal, Akmal; Maaruf, Siti Zuraida (2016)
Multicultural education is prevalent in the development of the new generation while createing awareness of living in a multiracial nation such as Malaysia (Sharifah Norsana, 2012). This study focuses on the development of multicultural Textile Interactive Module (McTIM) for secondary teachers in art classes. In order to achieve the research objective, this article will discuss on how to design and develop McTIM using the Delphi Technique. Areas pertaining to the rationale of using the Delphi Technique, criteria for the selection of the expert panel, panel size and determining the number of rounds are described and discussed in the context of this study. For the present study, the researchers used the Delphi Technique as a medium to select suitable activities which should be incorporated in this pedagogical module for textiles syllabus in the visual art education subject. Findings from this study revealed that the expert panel from various fields provided positive feedback and reached a consensus. They also agree with the researchers to design and develop this module for secondary school teachers